Geographical accessibility and duration of untreated psychosis: Distance as a determinant of treatment delay - Kvig, Erling Inge; Brinchmann, Beate; Moe, Cathrine Fredriksen; Nilssen, Steinar; Larsen, Tor Ketil; Sørgaard, Knut W. (BMC Psychiatry, 2017)
Source at http://dx.doi.org/10.1186/s12888-017-1345-8 Background: The duration of untreated psychosis is determined by both patient and service related factors. Few studies have considered the geographical accessibility of services in relation to treatment delay in early psychosis. To address this, we investigated whether treatment delay is co-determined by straight-line distance to hospital based specialist services in a mainly rural mental health context. Methods: A naturalistic cross-sectional study was conducted among a sample of recent onset psychosis patients in northern Norway (n = 62). Data on patient and service related determinants were analysed. Results: Half of the cohort had a treatment delay longer than 4.5 months. In a binary logistic regression model, straight-line distance was found to make an independent contribution to delay in which we controlled for other known risk factors. Conclusions: The determinants of treatment delay are complex. This study adds to previous studies on treatment delay by showing that the spatial location of services also makes an independent contribution. In addition, it may be that insidious onset is a more important factor in treatment delay in remote areas, as the logistical implications of specialist referral are much greater than for urban dwellers. The threshold for making a diagnosis in a remote location may therefore be higher. Strategies to reduce the duration of untreated psychosis in rural areas would benefit from improving appropriate referral by crisis services, and the detection of insidious onset of psychosis in community based specialist services.